An innovative method for automatic determination of time of arrival for Lamb waves excited by impact events. (13th April 2017) - Zhu, Junxiao; Parvasi, Seyed Mohammad; Ho, Siu Chun Michael; Patil, Devendra; Ge, Maochen; Li, Hongnan; Song, Gangbing
Abstract: Lamb waves have great potential as a diagnostic tool in the application of structural health monitoring. Propagation properties of Lamb waves are affected by the state of the structure that the waves are traveling upon. Thus Lamb waves can carry information about the structure as they travel across a structure. However, the dispersive, multimodal and attenuation characteristics of Lamb waves make it difficult to determine the time of arrival of Lamb waves. To deal with these characteristics, an innovative method to automatically determine the time of arrival for impact-induced Lamb waves without human intervention is proposed in this paper. Lead zirconate titanate sensors mounted on the surface of an aluminum plate were used to measure the Lamb waves excited by an impact. The time of arrival was determined based on wavelet decomposition, Hilbert transform and statistics (Grubbs' test and maximum likelihood estimation). Both of numerical analysis and physical measurements have verified the accuracy of this method for impacts on an aluminum plate.